Segmentação de mercados pelo estágio no ciclo de vida familiar: o modelo brasileiro - Saraiva Junior, Francisco Ilson (2010)
In spite of all discussion about the crisis in family as a institution due to the widespread changes which contemporary society has been undergoing such as the increase of single-person households, single-parent families headed by the mother, the older age for marrying for the first time, the growing number of unmarried couples cohabiting, the rise in the number of women in the job market and the growth in purchasing power of households, family has become a flexible concept term, which reflects the transitions from the rigid structure of the nuclear family to an addition of family forms and lifestyles. So the challenge is to look closer at the needs of diverse family structures and arrangements to better understand their needs and desires through various life events. This present study has explored the family life cycle as an important segmentation criteria, as it establishes consumption patterns over the life span. This paper reviews the family life cycle models which have been most referred in the literature in order to validate a model adapted to the particular characteristics of Brazil environment by considering the micro data of an empirical research made by Brazilian Institute for Geography and Statistics in 2002 and 2003. This article contributes to the fact that Brazil is endeavoring to find its own way to market its goods and services, with especial attention being given to market segmentation, instead of passively using foreign models. In spite of all discussion about the crisis in family as a institution due to the widespread changes which contemporary society has been undergoing such as the increase of single-person households, single-parent families headed by the mother, the older age for marrying for the first time, the growing number of unmarried couples cohabiting, the rise in the number of women in the job market and the growth in purchasing power of households, family has become a flexible concept term, which reflects the transitions from the rigid structure of the nuclear family to an addition of family forms and lifestyles. So the challenge is to look closer at the needs of diverse family structures and arrangements to better understand their needs and desires through various life events. This present study has explored the family life cycle as an important segmentation criteria, as it establishes consumption patterns over the life span. This paper reviews the family life cycle models which have been most referred in the literature in order to validate a model adapted to the particular characteristics of Brazil environment by considering the micro data of an empirical research made by Brazilian Institute for Geography and Statistics in 2002 and 2003. This article contributes to the fact that Brazil is endeavoring to find its own way to market its goods and services, with especial attention being given to market segmentation, instead of passively using foreign models.